LGG-17. DECREASED FUNCTION OF ISOPRENYLCYSTEINE CARBOXYLMETHYLTRANSFERASE RESULTS IN INCREASED SENSITIVITY TO CHEMORADIATION IN OLIGODENDROGLIOMA. (23rd April 2019) - Altshuler, David; Yadav, Vivekanand; Rosales, Maria Ventosa; Castro, Maria; Lowenstein, Pedro
Abstract: Oligodendroglioma is an indolent, chemosensitive glioma characterized by 1p/19q co-deletion. This loss of genetic information may be responsible for its unique treatment sensitivity. Our preliminary data suggests a role for the 1p gene, isoprenylcysteine carboxylmethyltransferase (ICMT). ICMT is the only enzyme to methylate prenylcysteine subtrates and has broad influence on lamin A function in the nucleus. We hypothesized that ICMT may be responsible for the unique treatment sensitivity of oligodendroglioma. An in vivo brain tumor model was established in ICMT knock-down transgenic mice whereby subventricular zone cells of neonates were transfected with oncogenic plasmids and a transposase to generate a tumor, recapitulating de novo glial oncogenesis. A Kaplan-Meier analysis was performed for mice treated with CCNU chemotherapy grouped according to ICMT expression levels from low to high by genotype (hypomorphic, heteromorphic, or wildtype). In vitro RNA interference studies were performed in glioma cell lines expressing a short-hairpin against ICMT. Procarbazine, carmustine, vincristine (PCV) and radiosensitivity assays were performed. The impact of ICMT inhibition on lamin A function was characterized by immunofluorescence. There was a significant difference in the median overall survival of CCNU treated transgenic mice by ICMT genotype. Hypomorphic mice had the longest median survival (91±29 days, n=9) compared to heteromorphs (78±19, n=14) and wildtype (72±44, n=16). In vitro, cells with ICMT inhibited demonstrated increased sensitivity to PCV and radiation. Lamin A immunofluorescence revealed disrupted nuclear membranes in ICMT-inhibited cells, suggesting potential increased sensitivity to DNA damaging agents. The 1p/19q co-deletion that is a characteristic of oligodendroglioma may be related to its unique treatment sensitivity. Preliminary in vivo and in vitro data implicate ICMT as a gene on chromosome 1p that may play an important role. Further characterization of the involved molecular mechanisms may lead to novel therapeutic strategies that exploit associated vulnerabilities in oligodendroglioma and other glial neoplasms. MEDULLOBLASTOMA